Efecto del acabado superficial en la resistencia a corrosión por picadura en un acero inoxidable martensítico (2024)
This paper investigates the impact of surface finish on the pitting corrosion resistance of a martensitic stainless steel. Since pitting corrosion is a critical phenomenon that compromises the structural integrity of materials in corrosive environments, a detailed analysis was carried out to understand how different surface finishes influence the susceptibility to pitting corrosion.